Answer:
![(g \: \circ \: f)(0) = 17](https://img.qammunity.org/2021/formulas/mathematics/college/ks55t54huqvsdg05pjdmpbcx71wm5o13yz.png)
Explanation:
f(x) = 2x + 4
g(x) = 4x² + 1
In order to find (g ∘ f)(0) we must first find
(g ° f )(x)
To find (g ° f )(x) substitute f(x) into g(x) that's for every x in g(x) replace it with f(x)
That's
![(g \: \circ \: f)(x) = 4( ({2x + 4})^(2) ) + 1 \\ = 4(4 {x}^(2) + 16x + 16) + 1 \\ = {16x}^(2) + 64x + 16 + 1](https://img.qammunity.org/2021/formulas/mathematics/college/j27fj3hp7qfl4mmw08ewtwt15mgod4xsrb.png)
We have
![(g \: \circ \: f)(x) = {16x}^(2) + 64x + 17 \\](https://img.qammunity.org/2021/formulas/mathematics/college/y049g29hc7jgh2tfbfze8t7ry0x3q6tb9w.png)
Now to find (g ∘ f)(0) substitute the value of x that's 0 into (g ∘ f)(0)
We have
![(g \: \circ \: f)(0) = 16( {0})^(2) + 64(0) + 17 \\](https://img.qammunity.org/2021/formulas/mathematics/college/qwxlhy46fbcyl48r9921q94hkdqqdyy5se.png)
We have the final answer as
![(g \: \circ \: f)(0) = 17](https://img.qammunity.org/2021/formulas/mathematics/college/ks55t54huqvsdg05pjdmpbcx71wm5o13yz.png)
Hope this helps you